2013
DOI: 10.1002/chem.201303538
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclobakuchiols A, B, and C by Using Conformation‐Controlled Stereoselective Reactions

Abstract: Cyclohexanone with the pMeOC6H4 and CH2=C(Me) substituents at the C3 and C4-positions was prepared from (+)-β-pinene and converted to the allylic picolinate by a Masamune-Wittig reaction followed by reduction and esterification. Allylic substitution of this picolinate with Me2CuMgBr·MgBr2 in the presence of ZnI2 proceeded with γ regio- and stereoselectively to afford the quaternary carbon center on the cyclohexane ring with the CH2=CH and Me groups in axial and equatorial positions, respectively. This product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…4 Although the ee was somewhat low, 12 conversion of 11 to cyclobakuchiols A and C would provide an opportunity to synthesize a certain set of analogs as well for biological investigation. Toward the end, the 1,4-addition of BF 3 $OEt 2 -activated enone 11 with (4-MeOC 6 H 4 ) 2 Cu(MgBr)$MgBr 2 afforded ketone 18, which was converted to ester 19 as a mixture of the olefinic isomers in 72% yield from enone 11 (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the ee was somewhat low, 12 conversion of 11 to cyclobakuchiols A and C would provide an opportunity to synthesize a certain set of analogs as well for biological investigation. Toward the end, the 1,4-addition of BF 3 $OEt 2 -activated enone 11 with (4-MeOC 6 H 4 ) 2 Cu(MgBr)$MgBr 2 afforded ketone 18, which was converted to ester 19 as a mixture of the olefinic isomers in 72% yield from enone 11 (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported 4 synthesis of cyclobakuchiols AeC (1e3), and elucidated the absolute configuration for each by comparing their specific rotations with those reported. Ketone 5, which is the intermediate for the synthesis of 1 and 2, was synthesized from (þ)-b-pinene (4) and subsequently transformed into allylic picolinate 6, which upon allylic substitution 5 with Me 2 Cu(MgBr)$MgBr 2 /ZnI 2 gave the methyl ether of 1 (Scheme 1). Furthermore, this ether was converted into 2 through epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The Prilezhaev (Prileschajew) method that uses m ‐chloroperoxybenzoic acid ( m CPBA) as an oxidant under mild conditions is applied to the epoxidation of botryococcene 1 , because it has been frequently used in the synthetic procedures of unstable natural products such as terpenoids ,. First, 1 is reacted with an excess amount of the oxidant so that all the C−C double bonds of 1 react.…”
Section: Figurementioning
confidence: 99%
“…[2,3,5b] Asecond tactic involves addition of the enolate nucleophile to av inyl surrogate such as vinyl sulfoxide, [6] (phenylseleno)acetaldehyde, [7] or ethylene oxide, [8] followed by elimination. However,t here are few reports of stereoselective additions that form the quaternary stereocenter, [9] and none are catalytic or enantioselective. Because of these constraints,e ven the simplest 2-methyl-2vinylcyclohexanone (7)isnot known as asingle enantiomer in the literature.…”
mentioning
confidence: 99%
“…Aside from keto acid substrates,w ee xamined acids bearing other types of carbonyl functionalities (entries 7-10), and found that the avinyl ester 9g,lactam 9h,and aldehyde 9i can all be prepared in good yields.More complex scaffolds such as 8j,obtained by oxidative cleavage of testosterone, [14] also undergo the reaction to provide the vinylated tricycle 9j (entry 11). While the reaction can be carried out in the absence of as olvent on af airly large scale (5 mmol, entries 1-7), we found that for smaller scale synthesis it is more convenient to use N-methylpyrrolidinone (NMP) as as olvent along with slightly modified reaction conditions (entries [8][9][10][11]. [15] To further demonstrate the utility of our decarbonylative dehydration approach to vinylation, we embarked on at otal synthesis of aspewentin B( 1,F igure 1), an orditerpene natural product isolated from Aspergillus wentii.…”
mentioning
confidence: 99%